PROSPEK PENGEMBANGAN BAWANG MERAH TIRON SEBAGAI KOMODITI UNGGULAN DAERAH ISTIMEWA YOGYAKARTA (DITINJAU DARI PREFERENSI KONSUMEN) - Sugiharti Mulya Handayani (Universitas Sebelas Maret, 2005)
The objective of this research is to find out onion's attributes which are preferred and considered by the costumers while buying a commodity. The method used in this research was analytical descriptive with survey technique in implementation The location was selected purposively